Overall leukocyte levels link risk factors to Von Willebrand factor and Neutrophil Extracellular Traps in stroke thrombi: a Structural Equation Modeling analysis - Shi, Lin; Wei, Chunxiao; Ye, Guowei; Zhao, Panpan; Ma, Shiqiang; Qi, Yiming; Zhou, Ruolin; Zhang, Yaru; Zhang, Yan; Meng, Lingjie; Xu, Weihang; Li, Chao; et al. (Frontiers in Neurology, 2025)
BackgroundVon Willebrand Factor (VWF) and Neutrophil Extracellular Traps (NETs) are involved in the inflammatory response during thrombi formation and are widely found in thrombi of Acute Ischemic Stroke (AIS) patients. Inflammation may mediate the relationship between cerebrovascular risk factors (such as blood glucose) and thrombi components. This study uses overall leukocyte levels to identify potential links between risk factors and VWF, NETs in thrombi.MethodsThrombi samples and clinical data from 61 stroke patients treated at our hospital between 2017 and 2023 were collected. The Partial Least Squares Structural Equation Modeling (PLS-SEM) assessed direct and indirect associations, with leukocyte and its subtype counts as mediating variables, VWF and NETs as endogenous variables, and cerebrovascular risk factors as exogenous variables.ResultsHeart dysfunction and blood glucose showed a significant negative indirect effect on VWF through the overall leukocyte levels (indirect effect = −0.119 and −0.118, p < 0.05). Overall leukocyte levels acted as a mediator between vitamin B12 and VWF levels in thrombi, displaying a positive mediatory impact (indirect effect = 0.118, p < 0.05). The decrease in VWF levels within thrombi was closely associated with an increase in discharge NIHSS scores (path coefficient = −0.353, p < 0.05). Additionally, overall leukocyte levels and homocysteine (Hcy) had significant negative effects on VWF (path coefficients = −0.384 and −0.308, p < 0.05), while vitamin B12 had a negative impact on NETs (path coefficient = −0.289, p < 0.05).ConclusionOverall leukocyte levels mediate the influence of blood glucose levels, heart dysfunction, and vitamin B12 on content VWF in thrombi in stroke patients. VWF reduction correlates with elevated discharge NIHSS scores. These cerebrovascular factors may regulate the pathological process of AIS thrombosis through inflammatory responses, guiding further exploration of the underlying mechanisms and informing clinical strategies.